Growth of cod (Gadus morhua) in the western Baltic Sea: estimating improved growth parameters from tag-recapture data - McQueen, Kate; Paige Eveson, J.; Dolk, Bodo; Lorenz, Thomas; Mohr, Thomas; Schade, Franziska Maria; Krumme, Uwe (Canadian Journal of Fisheries and Aquatic Sciences, 2019)
Tag–recapture data contain valuable information about individual fish growth, which can enhance the estimation of growth parameters. Tag–recapture data are especially useful when age-determination uncertainties throw age-based growth estimates and stock assessments into question, as is the present situation with several important gadoid stocks. Length-based (GROTAG method) and age-based (LEP method) growth functions were fit to a large data set of tagged and recaptured cod (Gadus morhua) from an artificial reef in the western Baltic Sea to calculate improved growth parameter estimates. The LEP method allowed integration of different data formats, including tag–recapture, length frequency, and length-at-age, to estimate a more robust and comprehensive growth function (von Bertalanffy growth parameters: L∞ = 154.56 cm, k = 0.11, t0 = –0.13). Two heavily exploited cod stocks inhabit the Baltic Sea, subsisting at the upper thermal and lower salinity limits of the species. Otolith shape analyses indicated that, unexpectedly, individuals from both populations were resident at the reef. Compared with cod populations elsewhere, cod in the western Baltic Sea grow relatively slowly and with weak seasonal fluctuations in growth rates, potentially due to adverse conditions for growth. Les données de marquage–recapture contiennent de l’information utile sur la croissance individuelle des poissons qui peut améliorer l’estimation des paramètres de croissance. Ces données sont particulièrement utiles quand les incertitudes associées à la détermination de l’âge jettent un doute sur les estimations de la croissance et les évaluations de stock basées sur l’âge, comme c’est actuellement le cas pour plusieurs stocks importants de gadidés. Des fonctions de croissance basées sur la longueur (méthode GROTAG) et sur l’âge (méthode LEP) ont été calées sur un grand ensemble de données de morues (Gadus morhua) marquées et recapturées d’un récif artificiel dans l’ouest de la mer Baltique afin d’obtenir de meilleures estimations des ...